Real Convergence of Western Balkan Countries to European Union in view of Macroeconomic Policy Mix - Aneta Krstevska (Journal of Central Banking Theory and Practice, 2018)
Western Balkan (WB) countries have a clear orientation towards the European Union (EU), all of them currently being candidate or potential candidate countries. Moreover, the EU is an important trading partner of the WB economies, therefore, there is a recognizable need for convergence of this region towards the EU economy. The real convergence is a rather slow process and the WB region is still lagging behind the EU. This paper explores the catch up of the WB region during the global crisis that severely hit the EU economy, trying to identify potential changes in the convergence pace. In addition, this work makes a joint overview of the nominal and real convergence processes as well as the convergence of the general macroeconomic indicators of the WB countries to the EU, taking them as complementary and mutually self-supporting processes.
Keywords: F15; O11; O57; 330; convergence; catch up; crisis; panel.